Moderating Effect of Materialism on the Inaction Inertia Phenomenon - Lee, Seongsoo; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: This study aims to investigate whether materialism tendency will act as a moderating variable for the inaction inertia phenomenon.Methods/Statistical analysis: A total of 121 college students were randomly assigned to 2 (difference in attractiveness condition: large vs. small) Ã— 2 (materialism: high vs. low) mixed design. Respondents read two-part scenario and responded to several questions: manipulation check item to assess perceived attractiveness, some questions related to regret (immediate regret, recalled experienced regret, anticipated inaction regret, anticipated action regret), behavioral intention, and demographics.Findings: First, the manipulation of the perception of difference in attractiveness (manipulated with price difference) was as the researcher intended. Immediate regret after missing the initial opportunity, recalled experienced regret, and anticipated action regret were found to be varied on the level of materialism. The level of recalled experienced regret, anticipated action regret, and anticipated inaction regret varied according to the difference in attractiveness conditions. The interaction effects of the level of materialism and difference in attractiveness conditions appeared only for anticipated action regret and anticipated inaction regret. Anticipated action regret and inaction regret were found to have a significant effect on behavioral intention regardless of the level of materialism. On the other hand, recalled experienced regret had a significant impact on behavioral intention only in low-materialist group.Improvements/Applications: This study has theoretical and practical implications from the point of view of how the various kinds of regrets vary according to materialism in the area of inaction inertia effect.Â Â